Transcriptional Control of Drug Resistance, Virulence and Immune System Evasion in Pathogenic Fungi: A Cross-Species Comparison - Pais, Pedro; Costa, Catarina; Cavalheiro, Mafalda; Romão, Daniela; Teixeira, Miguel C. (Frontiers in Cellular and Infection Microbiology, 2016)
Transcription factors are key players in the control of the activation or repression of gene expression programs in response to environmental stimuli. The study of regulatory networks taking place in fungal pathogens is a promising research topic that can help in the fight against these pathogens by targeting specific fungal pathways as a whole, instead of targeting more specific effectors of virulence or drug resistance. This review is focused on the analysis of regulatory networks playing a central role in the referred mechanisms in the human fungal pathogens Aspergillus fumigatus, Cryptococcus neoformans, Candida albicans, Candida glabrata, Candida parapsilosis and Candida tropicalis. Current knowledge on the activity of the transcription factors characterized in each of these pathogenic fungal species will be addressed. Particular focus is given to their mechanisms of activation, regulatory targets and phenotypic outcome. The review further provides an evaluation on the conservation of transcriptional circuits among different fungal pathogens, highlighting the pathways that translate common or divergent traits among these species in what concerns their drug resistance, virulence and host immune evasion features. It becomes evident that the regulation of transcriptional networks is complex and presents significant variations among different fungal pathogens. Only the oxidative stress regulators Yap1 and Skn7 are conserved among all studied species; while some transcription factors, involved in nutrient homeostasis, pH adaptation, drug resistance and morphological switching are present in several, though not all species. Interestingly, in some cases not very homologous transcription factors display orthologous functions, whereas some homologous proteins have diverged in terms of their function in different species. A few cases of species specific transcription factors are also observed.